2021
DOI: 10.3390/ijerph18020544
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of NO2 Pollution Level during the COVID-19 Lockdown in a Romanian City

Abstract: This study investigates changes in pollution associated with the lockdown period caused by the COVID-19 pandemic in Galati (45.43° N, 28.03° E), a Romanian city located in the southeast of Romania. The study is focused on nitrogen dioxide (NO2), a trace gas which can be related to emissions from industrial activities, heating, and transportation. The investigation is based on in situ observations from local Air Quality Monitoring Stations (AQMS) and mobile remote sensing observations by Differential Optical Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Research [33] used mobile technology based on measuring the effect of light absorption depending on the concentration of particles in the air. The area where the measurement was made is one of the biggest cities in Romania, with a large amount of traffic.…”
Section: Related Workmentioning
confidence: 99%
“…Research [33] used mobile technology based on measuring the effect of light absorption depending on the concentration of particles in the air. The area where the measurement was made is one of the biggest cities in Romania, with a large amount of traffic.…”
Section: Related Workmentioning
confidence: 99%
“…Secondly, the impact on environment generated by COVID-19 is important for Romanian residents [40], together with the social and economic impacts. So, studies on air pollution were carried out in other regions in Romania, such as in the capital city of Bucharest [41], in major cities in Northeastern Romania: Bacau [42], in Southeastern Romania: Galati [43] and in Central Romania: Brasov [44], but not in the Cluj area. The studies observed that the pandemic crises had limited positive effects on reducing the pollution generated by traffic, and not so much from industries, and, also, it was pointed out that the bigger the city, the better the positive effect of pollution reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Another case study conducted in Bucharest on NO 2 concentrations shows the same decreasing trend as in other cities in Europe, only some sudden increases could be observed due to fires in landfills [ 50 ]. NO 2 concentrations recorded at the in situ stations in the city of Galati (SE Romania), during the state of emergency, decreased between 10 and 40%, at some stations, being best highlighted during the working days [ 51 ]. In April 2020, during the state of emergency, the levels of PM 2.5 and PM 10 decreased also in Brașov, the most important tourist center in Romania [ 52 ].…”
Section: Introductionmentioning
confidence: 99%